Effectiveness of Government Regulation Number 22/2021 in Controlling Air Pollution from Brick-Making Industry - Pranata, Rifo Andi; Rahmatiar, Yuniar; Abas, Muhamad (UNISSULA, 2025)
The phenomenon of air pollution caused by the brick-making industry has become a pressing environmental issue demanding resolution. Various studies have shown that emissions from the brick-kiln process contribute significantly to the decline in ambient air quality in industrial areas and their surroundings. This study aims to evaluate the environmental impacts of brick-kiln operations and to assess the effectiveness of government policy implementation in controlling air pollution from the industrial sector. This study adopts a normative and empirical research paradigm as its primary methodological framework. A qualitative approach is used because of its ability to facilitate in-depth exploration of phenomena in the natural environment, with the researcher acting as the primary instrument for data collection and analysis. The result of this study are brick-kiln operations in Mekarmulya Village cause significant air, noise, and land degradation impacts, with the community gradually normalizing pollution due to weak regulatory oversight and limited institutional capacity in enforcing environmental policies for micro-enterprises. The study concludes that ineffective environmental governance and limited institutional capacity have allowed the micro-scale brick-kiln industry in Mekarmulya Village to cause significant pollution and land degradation, highlighting the need for the implementation of adaptive, socially aware, and inclusive environmental policies for the informal sector.